PENGARUH LEVERAGE & INTENSITAS MODAL TERHADAP MANAJEMEN PAJAK DI MODERASI OLEH UKURAN PERUSAHAAN(Emiten Consumer-Non Cyclicals Bursa Efek Indonesia Periode 2021 - 2023). - Adrian, Muhammad Rivki; Mukti, Aloysius Harry; Eprianto, Idel (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The study aims to examine the Effect of Leverage and Capital Intensity on Tax Management Moderated by Company Size. Population of Consumer-Non Cyclical Issuers of the Indonesia Stock Exchange for the 2021-2023 Period. The variables used in this study are Tax Management as the dependent variable; Leverage and Capital Intensity as independent variables; and Company Size as the Moderation variable. The sampling technique used was the purposive sampling method and obtained 74 Company samples. The analysis methods used were Descriptive Statistical Analysis, Classical Assumptions, Multiple Linear Analysis, Hypothesis Testing and Moderation Regression Analysis. The results of this study indicate that partially Leverage has a negative effect on Tax Management and Capital Intensity has no effect on Tax Management. The results of this study for the moderating variable, namely Company Size, are able to moderate (strengthen) the negative influence of Leverage on Tax Management and Company Size is not able to moderate Capital Intensity on Tax Management.